Physical barriers and environmental gradients cause spatial and temporal genetic differentiation of an extensive algal bloom. (1st February 2016) - Godhe, Anna; Sjöqvist, Conny; Sildever, Sirje; Sefbom, Josefin; Harðardóttir, Sara; Bertos‐Fortis, Mireia; Bunse, Carina; Gross, Susanna; Johansson, Emma; Jonsson, Per R.; Khandan, Saghar; Legrand, Catherine; et al.
Abstract: Aim: To test if a phytoplankton bloom is panmictic, or whether geographical and environmental factors cause spatial and temporal genetic structure. Location: Baltic Sea. Method: During four cruises, we isolated clonal strains of the diatom Skeletonema marinoi from 9 to 10 stations along a 1132 km transect and analysed the genetic structure using eight microsatellites. Using F ‐statistics and Bayesian clustering analysis we determined if samples were significantly differentiated. A seascape approach was applied to examine correlations between gene flow and oceanographic connectivity, and combined partial Mantel test and RDA based variation partitioning to investigate associations with environmental gradients. Results: The bloom was initiated during the second half of March in the southern and the northern‐ parts of the transect, and later propagated offshore. By mid‐April the bloom declined in the south, whereas high phytoplankton biomass was recorded northward. We found two significantly differentiated populations along the transect. Genotypes were significantly isolated by distance and by the south–north salinity gradient, which illustrated that the effects of distance and environment were confounded. The gene flow among the sampled stations was significantly correlated with oceanographic connectivity. The depletion of silica during the progression of the bloom was related to a temporal population genetic shift. Main conclusions: A phytoplankton bloom may propagate as a continuous cascade and yet be genetically structured over both spatial and temporal scales. The Baltic Sea spring bloom displayed strong spatial structure driven by oceanographic connectivity and geographical distance, which was enhanced by the pronounced salinity gradient. Temporal transition of conditions important for growth may induce genetic shifts and different phenotypic strategies, which serve to maintain the bloom over longer periods.